About America : how the United States is governed - Arnold, Paul A.
Summary: Comprehensive overview of the various levels of and institutions related to government in the U.S. "How the United States Is Governed" describes how federal, state, and local governments are elected, how they operate, and how the executive, legislative, and judicial branches of government relate under the U.S. constitutional system. It also highlights how nongovernmental organizations (NGOs) and other institutions allow Americans to influence and shape government policy.